Perceptions of Prospective Teachers on Posters with Social Themes - Karaahmet, Selma; Malbelegi, Faruk (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
We can’t know that can we change the world through the poster which is a product of graphic design but it is possible to make goodness for humankind by designing router and awareness posterssincethey can redirect and emphasize the ideas with mass media.The aim of this study, which is prepared with this opinion, is determine to prospective teachers’values ofperceptions from different classesand different departments.Teachers are so important to have ability to reach and teach all individuals in community. For this reason, in this study 80 prospective teachers will attendduring 2014-2015 school year in Education Faculties of OndokuzMayıs University and Marmara University. Four different social themed posters selected which contains different values like respect, peace, sensitivity and tolerance, to state how their opinion about social issues. These posters will show to participants and ask about their opinion. The results will evaluate with content analysis.